2004
DOI: 10.1080/jmf.16.3.146.157
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cardiac dysfunction in preterm premature rupture of membranes

Abstract: Preterm PROM is associated with changes in fetal cardiac function consistent with increased left ventricular compliance. These observations were also noted in fetuses with microbial invasion of the amniotic cavity. Our findings suggest that fetal cardiac function is altered in preterm PROM and, in particular, in cases with intra-amniotic infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 54 publications
3
46
0
2
Order By: Relevance
“…In uncontrolled diabetic pregnant women, Wong et al [24] also reported a reduction in the E/A ratios, mainly in the right ventricle, reflecting early fetal cardiac adaptation. In fetuses with premature rupture of membranes and microbial invasion of the amniotic cavity, Romero et al [25] showed an increment in E/A velocities and ratios in both cardiac ventricles, also indicating early cardiac dysfunction in these fetuses.…”
Section: Clinical Implications Of the E/a Ratios And Outflow Tractsmentioning
confidence: 99%
“…In uncontrolled diabetic pregnant women, Wong et al [24] also reported a reduction in the E/A ratios, mainly in the right ventricle, reflecting early fetal cardiac adaptation. In fetuses with premature rupture of membranes and microbial invasion of the amniotic cavity, Romero et al [25] showed an increment in E/A velocities and ratios in both cardiac ventricles, also indicating early cardiac dysfunction in these fetuses.…”
Section: Clinical Implications Of the E/a Ratios And Outflow Tractsmentioning
confidence: 99%
“…Preterm rupture of membranes, particularly in cases with intra-amniotic infection, is associated with changes in fetal cardiac function consistent with increased left ventricular compliance and systolic dysfunction measured as an increased E/A ratio [131,132], shorter ejection time [133], and ventricular strain [132]. …”
Section: Research and Clinical Applications Of Fetal Cardiac Functionmentioning
confidence: 99%
“…This condition has been operationally defined as an elevation in fetal plasma IL-6 concentration, and is a risk factor for spontaneous preterm labour, neonatal morbidity and mortality, as well as multisystemic involvement (cardiac dysfunction [419,420], adrenal stress response [421], neurologic injury [422][423][424][425][426][427][428][429][430][431][432][433][434][435][436][437][438], as well as lung disease [128,[439][440][441][442][443][444][445]) (Figure 3). The relevance of this is that the identification of the patient with intra-amniotic inflammation has become a priority to select a patient in whom tocolysis would be futile, and who may benefit from antimicrobial and anti-inflammatory agents.…”
Section: Inflammation As a Mechanism For Term And Preterm Parturitionmentioning
confidence: 99%